Market Size and Number of Firms with New Technology - Sugata Marjit; Krishnendu Ghosh Dastidar; Gouranga Gopal Das (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this paper, unlike the conventional wisdom, we demonstrate that the relationship between the size of the market and number of firms would be non-monotonic. While moderate rise in the size would force the local firms to exit and only the foreign firm rules, substantial rise in the size would accommodate all firms. Also, the possibility of survival increases if the local firms could differentiate their product more and then we drift towards the conventional result.
Keywords: L13; D40; F10; 330; product differentiation; free entry; Cournot; output; market size; technology; FDI